Studying the effects of asymmetry on the bending rigidity of lipid membranes formed by microfluidics - Karamdad,K; Law,R; Seddon,J; Brooks,NJ; Ces,O (Chemical Communications (London), 2016)
In this article we detail a robust high-throughput microfluidic platform capable of fabricating either symmetric or asymmetric giant unilamellar vesicles (GUVs) and characterise the mechanical properties of their membranes.